Pembuatan Sistem Informasi Inventaris Barang Untuk Karang Taruna - Khaerul Anam; Martanto; Ridho Nugraha; Vicky Pamungkas (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Karang Taruna, a youth organization at the village level, manages various assets and equipment to support its activities. However, inventory management has mostly been done manually, making it prone to data entry errors, loss of records, and difficulty in asset tracking. This project aims to design and implement a web-based Inventory Information System tailored to the needs of Karang Taruna. The implementation method includes initial observation of the current inventory process, system design using the waterfall method (analysis, design, implementation, testing), and training for Karang Taruna members. The system was developed using PHP programming language and MySQL database with core features including asset entry and withdrawal recording, asset tracking, report generation, and user and category management. The implementation results show that the system improves the accuracy and efficiency of inventory management. Karang Taruna members also showed enthusiasm in operating the system and understanding the importance of asset management digitalization. This information system marks a significant step in the digital transformation of youth organizations in rural areas and can be replicated in similar organizations elsewhere. recommended.